Diagnosis of Types of Diseases in Cassava Plant by Bayes Method - Sidik, Agung Purnomo (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2019)
This research was conducted to implement the Bayes algorithm in an expert system to diagnose types of diseases in cassava plants. The research data was taken from the Binjai City Agriculture and Fisheries Office in 2018. The expert system was built based on the web, where the application was built using the PHP programming language and MySQL DBMS. The results showed that the Bayes algorithm can be used in expert system applications to diagnose types of cassava plant diseases. In the Bayes algorithm, the knowledge base is taken from the data of the amount of data from cassava plants that suffer from disease, so the results of diagnosing cassava plants are based on existing data. Therefore, the more patient data that is used as a knowledge base, the better the diagnosis results are given.